REQUESTIVE STRATEGIES PERFORMED BY PAPUAN STUDENTS IN SUNDANESE CULTURAL CONTEXT - Iis Sopiah; Fahrus Zaman Fadhly (English Review: Journal of English Education, 2016)
This study investigated requestive strategies performed by Papuan students and the effect of interlocutor’s cultural background on the way of Papuan students in making request. There were 16 Papuan students studying in senior high school and vocational high school in Kuningan participated in this study. The data were collected by using Discourse Completion Test (DCT) and interview. The theory of requestive strategies proposed by Blum-Kulka, House and Kasper (1989) and the theory of request modification proposed by Blum-Kulka Olshtain (1984) were used to analyze the data. The finding revealed that Papuan students used different strategy in making request to different interlocutor. Strategies mostly used by them while making request to Papuan was mood derivable. While making request to Sundanese, they tended to use query preparatory strategy. This finding also revealed that Papuan students tended to use more request modification when making request to Sundanese people. Those modifications involved (1) internal modifications, such as the use of interrogative, negation embedded if clause and negation, and (b) external modifications, such as the use of additional statements prior or after the head acts.Keywords: Requestive strategies, request modification, Papuan students, Sundanese.